Pengaruh Minuman Segar Buah Etlingera hemisphaerica (MSBE) terhadap Kadar Asam Urat dan Kolesterol Warga Kabupaten Lebong dan Kepahiang - Susanti, Reka; Karyadi, Bhakti; Parlindungan, Deni; Ruyani, Aceng (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Fresh fruit drink Etlingera hemisphaerica (forest honje; MSBE) has been produced, and has obtained a distribution permit in the community. It is deemed necessary to study the benefits of MSBE. This limited clinical study aims to determine the effect of MSBE administration on uric acid and cholesterol levels in residents of Lebong and Kepahiang Regencies, Bengkulu Province. Five (5) men from Lebong and five (5) men from Kepahiang who were involved as probands in limited clinical research. Initial levels of uric acid and cholesterol for each probandus were measured by Auto Check. Each probandus was asked to consume MSBE once a day for seven (7) days. On the 8th day, the probandus uric acid and cholesterol levels were measured again by Auto Check. The levels of uric acid and cholesterol before and after the probandus consumed MSBE were then compared. Uric acid levels in 10 probands before (5.95 ± 1.48 mg/dL) and after (6.56 ± 1.64 mg/dL) MSBE consumption tended to increase but were not significantly different. Uric acid levels in Lebong residents before (6.40 ± 1.78 mg/dL) and after (6.60 ± 1.42 mg/dL) tended to increase but were not significantly different, while uric acid levels in Lebong residents before (5.50 ± 1.10 mg/dL) and after (6.52 ± 2.01 mg/dL) tended to increase but not significantly different. Cholesterol levels in 10 probands before (144.30 ± 17.38 mg/dL) and after (147.60 ± 29.53 mg/dL) MSBE consumption tended to increase but were not significantly different. Cholesterol levels in Lebong residents before (134.00 ± 17.99 mg/dL) and after (166.40 ± 18.73 mg/dL) tended to increase but were not significantly different, while cholesterol levels in Lebong residents before (154.60 ± 9.53 mg/dL) and after (128.80 ± 26.97 mg/dL) tended to decrease but not significantly different. MSBE consumption for one week had no significant effect on probandus uric acid and cholesterol levels. Cholesterol levels in Kepahiang residents tend to decrease after consuming MSBE.